2018
DOI: 10.18203/2320-1770.ijrcog20183343
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of maternal serum vitamin D levels and its correlation with gestational diabetes mellitus

Abstract: Background: Several studies in the past two decades have proved beyond doubt that there is a high prevalence of hypovitaminosis D worldwide including India which has almost taken the shape of a pandemic. The study aims to determine the prevalence of hypovitaminosis D in the pregnant population of Delhi and its correlation with gestational diabetes mellitus.Methods: This prospective cross sectional observational study was conducted at the Department of Obstetrics and Gynaecology, Postgraduate Institute of Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…18 Another case control study done by Narain et al revealed that the prevalence of vitamin D deficiency was 86.25% where the mean serum vitamin D levels in the case and control group were 11.65 ng/ml and 14.4 ng/ml respectively but it was not statistically significant (P-value= 0.339). 19 Most of the studies with few exceptions revealed low levels of serum vitamin D level among the GDM patients. So, we can take some measures like proper food consumption, vitamin D supplementation and lifestyle modification to overcome vitamin D deficiency to prevent GDM and thereby improve the maternal and perinatal outcome.…”
Section: Discussionmentioning
confidence: 96%
“…18 Another case control study done by Narain et al revealed that the prevalence of vitamin D deficiency was 86.25% where the mean serum vitamin D levels in the case and control group were 11.65 ng/ml and 14.4 ng/ml respectively but it was not statistically significant (P-value= 0.339). 19 Most of the studies with few exceptions revealed low levels of serum vitamin D level among the GDM patients. So, we can take some measures like proper food consumption, vitamin D supplementation and lifestyle modification to overcome vitamin D deficiency to prevent GDM and thereby improve the maternal and perinatal outcome.…”
Section: Discussionmentioning
confidence: 96%